Comparison of general practice residents' attitudes and perceptions about training in two programmes in China: a mixed methods survey. Issue 4 (24th November 2019) - Lian, Siqing; Xia, Yu; Zhang, Jinzhi; Han, Xiaoning; Chi, Chunhua; Fetters, Michael D
Abstract : Objective: To understand general practice (GP) residents' attitudes about their residency training in China. Design: Mixed methods survey administered cross-sectionally. Setting: Two GP training programmes similar in most regards according to current GP training policy of 5 years' undergraduate degree in medicine and 3 years of postgraduate GP residency training—but differing as the Beijing programme has adopted educational innovations beyond the nationally prescribed standard curriculum used by the second Shenzhen programme. Participants: 105 (85%) of eligible GP trainees, 35 (90%) in the innovative Beijing programme and 70 (83%) in the standard training Shenzhen programme. Results: Overall, residents felt discrimination because of specialty choice, and that they lacked competency as a general practitioner. Many residents commented faculty had negative teaching attitudes. Beijing residents were more satisfied than Shenzhen residents with their training (p=0.001), and felt teaching faculty had sufficient knowledge (p<0.001), and appropriate attitudes towards teaching (p=0.004). Beijing residents more strongly agreed on five items about good future job prospects (all p<0.05). Conclusion: These Chinese GP residents identify areas for improvement in their training as well as strengths. Higher satisfaction with faculty teaching and job optimism in Beijing where GP residents receive training from specifically qualified faculty, and can earn special certification, suggest that the educational innovations enhance training and promote positivity about job prospects. These findings imply that GP residents in China face many training challenges that are similar to other international reports, while also implicating benefits of using an innovative curricular approach.